Penerapan Gaya Penyutradaraan Realisme dalam Film Fiksi Pemutus Siklus Sebagai Representasi Dampak Sosial Konsumsi Ballo’ di Kecamatan Bulukumpa - Muh Hidayat; Sulfiana Mansyur Putria (Journal of Media and Communication | E-ISSN : 3063-9581, 2026)
The consumption of ballo' or palm wine in Bulukumba Regency, particularly in Bulukumpa District, has become a traditional custom and is considered part of the local cultural heritage. Some people believe that ballo' functions as a natural stimulant and a way to relieve fatigue after a long day's work. Its close presence in community life makes ballo' consumption considered commonplace in various social activities. However, behind this positive view, excessive consumption of palm wine often has negative impacts, such as loss of self-control that triggers criminal acts, ranging from domestic violence (KDRT) and thuggery to murder. This condition makes ballo' not only seen as a cultural heritage, but also as one of the triggers for the emergence of various social problems in society. Departing from this phenomenon, the fictional film Pemutus Siklus is presented as a medium for social reflection that aims to voice the director's concerns while building collective awareness in society, especially the younger generation, to be more critical of the culture passed down through generations. This film uses a realist directing style by presenting people's lives naturally without excessive dramatization through characters, dialogues, settings, and events that resemble everyday reality. The creative methods used are observation, field research, interviews, and visual exploration to obtain an authentic representation of people's lives. In its application, this film uses André Bazin's theory of realism which emphasizes the integrity of reality through the use of long takes, deep focus, and natural mise-en-scène so that the audience can feel an emotional closeness to the events shown. Through this approach, the film Pemutus Siklus is expected to be a medium for social reflection that presents a stronger, more natural, and more emotional viewing experience.